Nanoparticles integrated electro-conductive extiles - Parvez, Md. Shohan; Rahman, Md Mustafizur; Shah, Md. Jakaria; Parsha, Iftekharul Islam; Moniruzzaman, M. (Springer Nature, 2025)
Nanoparticles, with their unique physical and chemical properties, offer numerous possibilities for enhancing textile performance by introducing novel functionalities and addressing pressing challenges in various prospective areas. Electro-conductive smart textiles are one of the key possibilities of such innovation. Various conductive nano-materials, including metals, organic, inorganic, and conductive polymers, are integrated with conventional textile matters in the form of dip coating, electrospinning, printing, polymerization, and embroidery to induce conductivity in inert textile materials. It is observed that integrating these materials in nano-sized form with conventional textiles enables efficient electrical attributes without sacrificing the innate comfort and permeability of the textile. The resulting materials possess unique characteristics, including a lightweight design, superior sensitivity, and tunable conductivity. This configuration enables smart clothing capable of real-time tracking of vital signs, flexible power storage, and integrated sensors for detecting pressure, movement, or environmental changes, with potential applications in sports, military, and environmental monitoring. However, the advanced functionalization of conductive clothing also requires uniform distribution, minimization of bulk, flexibility, robust functionality, enduring comfort, launderability, and durability. The utilization of conductive nanoparticles, the incorporation technique, and stability with textiles require meticulous consideration, along with health and environmental considerations. This chapter examines the principles, fabrication techniques, and influencing factors of electroconductive textiles composed of conductive materials in nanoform. Finally, the projected futuristic application, adoption, and challenges of nanoparticles in wearable e-textiles will be briefly discussed.